An Adaption of the Endangered Togutil Tribe’s Local Wisdom into an Animation Character Design - Dominika Anggraeni Purwaningsih (Universitas Multimedia Nusantara, 2018)
As an archipelago state, Indonesia is full of diversity, home to numerous different ethnic groups, culture, and languages. However, this diversity has been neglected by both the government and citizens. In fact, in North Moluccas, East Halmahera forest, there is a primitive tribe which is endangered, named Togutil. Therefore, we try to package the life of Togutil tribe and their challenges into a character for animated films in a unique way. Animation has become one of the education tools aside from literacy media. Animation was chosen as a medium to reach all ages and convey the message in interesting ways. Each character has its own background aside from the main storyline. This creates a strong impression of the character to the viewer. Iconic character not only can attract the viewer, but also popularize a culture. The strength of character can be used as a medium to introduce a culture, such as the endangered Togutil tribe. Through creative imagination, the local wisdom of Togutil tribe can be packed into a unique character design. For example, the age of Togutil which is relatively young compared to other primitive tribe can be packed into the form of a child. The unique design not only attracted the viewer, but also introduce the existence of Togutil tribe itself.